Stabilization of Loess Using Nano-SiO(2) - Kong, Ran (Materials (Basel), 2018)
Improving the performance of loess is of significant importance for lowering its collapsibility and water sensitivity to construction requirements and for geohazard mitigation. The present paper studies the changes in mechanical, structural, and mineralogical properties of nano-SiO(2)-treated loess with different contents and curing days. The mechanical behavior was examined by unconfined compressive strength (UCS) of untreated and treated loess. To better understand the mechanisms of stabilization, particle size distributions, scanning electron microscope (SEM) images, and X-ray diffraction (XRD) analyses were carried out. The results show that the UCS increase with increasing contents and curing days due to nano-SiO(2) addition produced coarser particles, denser packing, and smaller pores in treated loess. The changes in the properties can be attributed to the formation of aggregation and agglomeration, with greater particle sizes and more interparticle contact. In addition, the results from mineralogical component analysis further confirm that physical structure modification controls the changes in mechanical and fabric properties, rather than chemical component alteration. Even small nano-SiO(2) additions can also provide great improvement when curing days are enough for the treated loess. These findings reveal that nano-SiO(2) has the potential to serve as a cost-effective stabilized additive that treats the universal loess.